Urban Ecomuseum: From song to scream, silence (Palíndromo, 2024)
This article focuses on a 24-hour journey, divided into four days of walking, carried out by the Urban Ecomuseum, an existential incursion by artists Cláudia Zanatta and Vado Vergara, after a storm in Porto Alegre. Based on the walk as a methodology, a reading of Homer's Odyssey and a planting carried out in the city's public space, the arguments are woven using the montage method proposed by Walter Benjamin to reflect on the changes in this urban center and their impact on the imaginary. It also asks how what is at the origin of the Homeric narrative reverberates as a project of domination as order in the contemporary city, relating it to a proposal in contemporary art.
Keywords: contemporary city; public space; montage; walk; Odyssey